Pelaksanaan Kegiatan Ekstrakurikuler Seni Musik (Calempong) di SMP Negeri 1 Siak Hulu - Jihan Muthiah; Tengku Ritawati (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
Extracurricular music activities at SMP Negeri 1 Siak Hulu are specifically research conducted to find out how the implementation of extracurricular music activities includes goals, materials, methods, facilities and infrastructure as well as evaluation and assessment in extracurricular music activities. The data collection technique used in using interview, observation and documentation techniques to find out directly the implementation of extracurricular music activities at SMP Negeri 1 Siak Hulu. Then the results of observation and interviews that have been conducted in this study are described and described. The material taught is calempong musical instrumens. The teaching method used is the lecture method and coupled with practice. Based on the results of the analysis of student learning, which amounted to 4 students consisting of class VII, it shows that most of the students who participated in this extracurricular music received an A (Very Good) grade, because this method made students feel quite understanding and interested in the material taught, students alson often practiced together and discussed the notes they did not understand. So that this extracurricular music activity at SMP Negeri 1 Siak Hulu also runs very well.